2014
DOI: 10.3389/fpsyg.2014.00551
|View full text |Cite
|
Sign up to set email alerts
|

Implicit learning modulates attention capture: evidence from an item-specific proportion congruency manipulation

Abstract: A host of research has now shown that our explicit goals and intentions can, in large part, overcome the capture of visual attention by objects that differ from their surroundings in terms of size, shape, or color. Surprisingly however, there is little evidence for the role of implicit learning in mitigating capture effects despite the fact that such learning has been shown to strongly affect behavior in a host of other performance domains. Here, we employ a modified attention capture paradigm, based on the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Their experiments involved designs that were different from our own, and we view our present efforts as an opportunity to supply converging evidence and draw in theoretical and methodological considerations from the proportion congruent literature that may be valuable for understanding evidence of contextual control in the attention-capture domain. Finally, our efforts to draw connections between the proportion congruent and attention-capture literatures are spread between this article and a companion article (Thomson, Willoughby, & Milliken, 2014) exploring more detailed aspects of the general methods presented here.…”
mentioning
confidence: 99%
“…Their experiments involved designs that were different from our own, and we view our present efforts as an opportunity to supply converging evidence and draw in theoretical and methodological considerations from the proportion congruent literature that may be valuable for understanding evidence of contextual control in the attention-capture domain. Finally, our efforts to draw connections between the proportion congruent and attention-capture literatures are spread between this article and a companion article (Thomson, Willoughby, & Milliken, 2014) exploring more detailed aspects of the general methods presented here.…”
mentioning
confidence: 99%
“…As a result, ignoring or suppressing the uninformative cues may not have been required in order to perform well. Indeed, recent studies [22,40] showed that attentional capture was only suppressed if task requirements were such that capture would interfere with target processing. Moreover, a study in macaques showed that modulations of V1 attention responses were larger for tasks that were more difficult [12].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, ignoring or suppressing the uninformative cues may not have been required 21 in order to perform well. Indeed, recent studies [22,41] showed that attentional capture was only suppressed if task requirements were such that capture would interfere with target processing. Moreover, a study in macaques showed that modulations of V1 attention responses was larger for tasks that were more difficult [12].…”
Section: Discussionmentioning
confidence: 99%